A terbium(iii) lanthanide–organic framework as a platform for a recyclable multi-responsive luminescent sensor. Issue 8 (7th February 2017) - Chen, Min; Xu, Wen-Ming; Tian, Jia-Yue; Cui, Hui; Zhang, Jiao-Xing; Liu, Chun-Sen; Du, Miao
Abstract : A terbium (iii ) lanthanide–organic framework provides a platform for a recyclable multi-responsive luminescent sensor for detecting Fe 3+, MnO4 −, Cr2 O7 2−, and p -nitrotoluene (4-NT), which is the first reported MOF-based sensor for detecting explosive 4-NT. Abstract : A terbium(iii ) lanthanide–organic framework (534-MOF-Tb) with a green-emission signal was successfully obtained by the solvothermal reaction of Tb 3+ ions with the organic ligand H3 TBOT (2, 4, 6-tris[1-(3-carboxylphenoxy)ylmethyl]mesitylene). 534-MOF-Tb contains microporous quadrangle channels with accessible Lewis-base sites and coordinated water molecules, which are feasible to anchor and recognise multifarious analytes. It can serve as a recyclable multi-responsive sensing material for detecting Fe 3+, MnO4 −, Cr2 O7 2−, and p -nitrotoluene (4-NT). Significantly, this is the first reported MOF-based sensor for detecting explosive 4-NT. Moreover, the mechanism of the selective luminescence quenching response for Fe 3+, MnO4 −, Cr2 O7 2− or 4-NT can be mainly explained in terms of the competition between the absorption of the light source energy and the electronic interaction between the analyte and the TBOT ligand.